Using lexical ontology for semi-automatic logical data warehouse design - Mior Nazri, Mior Nasir; Noah, Shahrul Azman; Hamid, Zarinah (Springer-Verlag, 2010)
Data Warehouse has become a very important tool for data analysis but the conversion from Operational Database to Data Warehouse is very complex. This paper presents a new method to design a data warehouse multidimensional model based on supply driven framework. We propose a semi-automatic tool using lexical ontology as the knowledge domain. The tool is able to identify fact and dimensional tables using the knowledge domain. Once fact table is identified, the following step is to generate Data Warehouse multidimensional model with minimal user interaction. The feasibility of the proposed method is demonstrated by a prototype using WordNet as knowledge domain.